The Impact of Financial Literacy and Digital Financial Access on the Sustainability of MSMEs - Nuraisah Nuraisah; Chairul Adhim; Fahrul Mauzu (Advances in Managerial Auditing Research, 2026)
Purpose: This study aims to examine the hypotheses regarding the effect of financial literacy and digital financial access on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in the stationery store sector in Dompu Subdistrict. Research Method: This study uses an associative quantitative approach. From a population of 154 business actors, 40 respondents were selected using purposive sampling. Data were collected through questionnaires and documentation, then analyzed using multiple linear regression in SPSS. Results and Discussion: The statistical test results indicate that financial literacy has a positive and significant effect on MSME sustainability. Meanwhile, digital financial access has a positive but not yet significant effect, indicating that business actors' use of technology is currently not fully optimized. Implications: MSME actors are advised to start integrating digital services not only for transactions but also for financial management. Local governments need to design technological assistance programs to support MSME sustainability. Originality: This study provides specific empirical evidence regarding digital adaptation and managerial capabilities in the stationery trade sub-sector within developing regions that are currently in the digitalization transition phase.